Repression of the genes for lysine biosynthesis in Saccharomyces cerevisiae is caused by limitation of Lys14-dependent transcriptional activation. - Feller, A (1994)
The product of the LYS14 gene of Saccharomyces cerevisiae activates the transcription of at least four genes involved in lysine biosynthesis. Physiological and genetic studies indicate that this activation is dependent on the inducer alpha-aminoadipate semialdehyde, an intermediate of the pathway. The gene LYS14 was sequenced and, from its nucleotide sequence, predicted to encode a 790-amino-acid protein carrying a cysteine-rich DNA-binding motif of the Zn(II)2Cys6 type in its N-terminal portion. Deletion of this N-terminal portion including the cysteine-rich domain resulted in the loss of LYS14 function. To test the function of Lys14 as a transcriptional activator, this protein without its DNA-binding motif was fused to the DNA-binding domain of the Escherichia coli LexA protein. The resulting LexA-Lys14 hybrid protein was capable of activating transcription from a promoter containing a lexA operator, thus confirming the transcriptional activation function of Lys14. Furthermore, evidence that this function, which is dependent on the presence of alpha-aminoadipate semialdehyde, is antagonized by lysine was obtained. Such findings suggest that activation by alpha-aminoadipate semialdehyde and the apparent repression by lysine are related mechanisms. Lysine possibly acts by limiting the supply of the coinducer, alpha-aminoadipate semialdehyde.